2007
DOI: 10.1074/jbc.m607613200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Repressor GFI-1 Antagonizes PU.1 Activity through Protein-Protein Interaction

Abstract: Mice lacking the zinc finger transcriptional repressor protein GFI-1 are neutropenic. These mice generate abnormal immature myeloid cells exhibiting characteristics of both macrophages and granulocytes. Furthermore, Gfi-1 ؊/؊ mice are highly susceptible to bacterial infection. Interestingly, Gfi-1 ؊/؊ myeloid cells overexpress target genes of the PU.1 transcription factor such as the macrophage colony-stimulating factor receptor and PU.1 itself. We therefore determined whether GFI-1 modulates the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…The same study found that Gfi-1 represses the Egr-2 promoter, providing cross-inhibition that stabilizes the neutrophil fate. Gfi-1 also directly interacts with and represses trans-activation by PU.1, providing an additional mechanism favoring granulopoiesis (Dahl et al, 2007).…”
Section: Retinoic Acid and Vitamin D Receptorsmentioning
confidence: 99%
“…The same study found that Gfi-1 represses the Egr-2 promoter, providing cross-inhibition that stabilizes the neutrophil fate. Gfi-1 also directly interacts with and represses trans-activation by PU.1, providing an additional mechanism favoring granulopoiesis (Dahl et al, 2007).…”
Section: Retinoic Acid and Vitamin D Receptorsmentioning
confidence: 99%
“…15,18,29,32 Gfi1 and Gfi1b also interact physically with other transcription factors through their zinc fingers to co-regulate gene expression (Figures 1 and 2). 17,29,[33][34][35][36] For example, Gfi1 interacts directly with ETS1 to repress the Bax gene through adjacent DNA binding sites. 33 Gfi1 may also mediate repression independently of DNA binding through interactions with the transcription factors Miz-1 and Pu.1.…”
Section: Structure and Expression Regulation Of Gfi1 And Gfi1b Proteinsmentioning
confidence: 99%
“…33 Gfi1 may also mediate repression independently of DNA binding through interactions with the transcription factors Miz-1 and Pu.1. 34,35 Similarly, Gfi1b controls the activity of the transcription factor GATA1 through direct protein-protein interactions on the DNA. 17,37 Apart from transcription regulation, Gfi1 also regulates protein expression at another level.…”
Section: Structure and Expression Regulation Of Gfi1 And Gfi1b Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase reporter assays QT6 or HEK293 cells on 24-well plates were transfected with PUx3-TK81-Luc (Ano et al, 2004), pFR-Luc (Stratagene, La Jolla, CA, USA) or pGL3-M-CSFR-Luc (Dahl et al, 2007) luciferase reporter construct (50 ng/well), together with effector plasmids (DEB-PU.1 (Ano et al, 2004), pCMV-T7-wtcSki, pCMV-T7-mt-cSki, pM or pM-PU.1) as indicated in the figure legend. The total amount of transfected DNA was equalized with pEGFP-C1 (vector, Clontech).…”
Section: Methodsmentioning
confidence: 99%